Memory of people from missing person posters: the number of posters seen, the number of times they are seen, and the passage of time matter. Issue 8 (14th September 2021) - O'Brien, Freya; Thorley, Craig
ABSTRACT: Missing person posters ask the public to monitor their environment for missing people and alert the authorities if they are encountered. Here, a single laboratory-based study examined whether the number of missing person posters someone sees, the number of times the posters are seen, and the time delay between seeing the posters and later encountering the missing people from them all influence the likelihood of the missing people being recognised and authorities alerted. To examine this, participants saw four or 12 missing person posters once, three, or five times and were asked to alert the researchers if any missing people later appeared in the study. Shortly after, or after a minimum of a 24-hr delay, the participants had to sort pictures of 40 people by gender. Four of these 40 people had appeared on the missing person posters. Participants were more likely to recognise the missing people and alert the researchers of this when they had seen four posters three or five times and when the missing people were encountered shortly after seeing the posters. When the posters were seen once, however, the number of posters seen did not impact performance. The applied implications of these findings are discussed.